JURANDIR AND NIETZSCHE: NIHILISM IN THE AMAZON - das Chagas Lacerda, Oclécio (Seven Editora, 2025)
In this article, i intend to synthesize the main concepts developed in my doctoral thesis, defended in August 2022, entitled: “The reception of Nietzsche's thought in the literary work of Dalcídio Jurandir”. For this purpose, I speak such conceptions, which should, in turn, justify the following thesis: the main characters of Jurandir manifest a type of nihilism, with signs and symptoms of European nihilism, diagnosed by Nietzsche. In this way, right from the start, I identify the type of reception of Nietzsche's philosophy, carried out by Jurandir. Then, I analyze the manifestation of nihilism in his novels, more specifically, in Chove nos campos de Cachoeira, Marajó e Belém do Grão Pará.DOI: https://doi.org/10.56238/sevened2025.029-048